2022
DOI: 10.1039/d2cp02725a
|View full text |Cite
|
Sign up to set email alerts
|

Trends in angle-resolved molecular photoelectron spectroscopy

Abstract: In this perspective article, main trends of angle-resolved molecular photoelectron spectroscopy in the laboratory up to the molecular frame, in different regimes of light-matter interactions, are highlighted with emphasis on foundations and most recent applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 457 publications
(799 reference statements)
0
5
0
Order By: Relevance
“…Further details are discussed below, with a realistic example case forming the basis of section 4.1. (For further introductory discussion and examples of LF and MF PADs, see [11,15]; a recent review article can be found in [26]. )…”
Section: Photoelectron Flux In the Lf And Mfmentioning
confidence: 99%
See 3 more Smart Citations
“…Further details are discussed below, with a realistic example case forming the basis of section 4.1. (For further introductory discussion and examples of LF and MF PADs, see [11,15]; a recent review article can be found in [26]. )…”
Section: Photoelectron Flux In the Lf And Mfmentioning
confidence: 99%
“…The steps in the process are depicted in figure 4, which label's primary inputs as the 'AF/LF measurements', referring to the βu LM (t), and the ADMs A K QS (t) calculated for a grid of fluence and temperature values by solving the TDSE using the appropriate Hamiltonian for impulsive alignment [41,44]. The 'Alignment Retrieval' process requires solving the linear equations (26) for the CLM KQS using these primary inputs over the entire gird of ADMs, and comparing to the measured data to find the bets fit solution. This provides the vector C lab needed for the next step-solving the linear equations (28).…”
Section: Mf Reconstruction Via Matrix Inversionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that time-resolved photoelectron spectroscopy can be applied to probe ultrafast electronic and nuclear molecular dynamics [43,[66][67][68][69][70][71]. However, angle-unresolved photoelectron spectra do not carry any spatial information about the dynamics, which is lost due to angle averaging.…”
Section: Introductionmentioning
confidence: 99%